Godaan Versus Integritas Seorang Hakim dalam Cerpen “Yang Mulia” Karya Insan Budi Maulana (Pendekatan Psikoanalisis Sigmund Freud) - Fajrul Falah (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2021)
This research is based on the short story "Yang Mulia" by Insan Budi Maulana, indicated to reflect the reality of law enforcement practices.  There are unethical practices carried out by law enforcers (judges). This unethical practice becomes biased because it is done by many people and becomes collective knowledge. Therefore, the problem in this study is how the inner turmoil of the characters (id, ego, superego) in the short story. Does Hakim Subakti work to have integrity or is he hesitant to face temptation. This study aims to reveal the id, ego, superego of the characters in the short story. The research approach used was Sigmund Freud's psychoanalysis. The qualitative descriptive research method was used to analyze the data. The words, phrases and sentences in the short stories are interpreted with a literary psychology approach. The results showed that Hakim Subakti's inner turmoil when he was rewarded by party litigants. Money (reward) is able to change a judge who initially has integrity (superego dominant), becomes doubtful and tempted (toward the id and dominant ego).